2021
DOI: 10.1186/s12884-020-03489-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of antenatal care and skilled birth attendance services utilization among childbearing women in Guinea: evidence from the 2018 Guinea Demographic and Health Survey data

Abstract: Background Globally, maternal health remains a major priority. Most of maternal deaths globally occur in sub-Saharan Africa, with most of these deaths linked to lack of access to antenatal care and skilled assistance during delivery. This study assessed the determinants of antenatal care and skilled birth attendance services utilization among childbearing women in Guinea. Methods Data for this study were obtained from the 2018 Guinea Demographic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
37
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 54 publications
(79 reference statements)
12
37
2
Order By: Relevance
“…The odds of not attending antenatal care service were reduced when educational status is increased. The nding was supported by previous researches in Western Ethiopia (62), Ethiopia(56), rural Ethiopia(51), Kenya (90), Guinea (55,91), Afghanistan (64), Angola (54), East African countries (60), India (92,93), Ghana (94), Nepal (95), Nigeria (96). Educated women might empowered to get services (97)(98)(99)(100)(101)(102), education make women to have decision making (103,104).…”
Section: Discussionsupporting
confidence: 80%
“…The odds of not attending antenatal care service were reduced when educational status is increased. The nding was supported by previous researches in Western Ethiopia (62), Ethiopia(56), rural Ethiopia(51), Kenya (90), Guinea (55,91), Afghanistan (64), Angola (54), East African countries (60), India (92,93), Ghana (94), Nepal (95), Nigeria (96). Educated women might empowered to get services (97)(98)(99)(100)(101)(102), education make women to have decision making (103,104).…”
Section: Discussionsupporting
confidence: 80%
“…Age of woman, education, polygyny status, wanted last-child, parity, death of a previous child, health insurance, household wealth index, urban-rural residence, and region of residence were treated as explanatory variables as seen in Table 1 . We selected the variables from the datasets based on their reported significance to the outcome variable in the literature [ 5 , 22 , 23 ]. All variables were available in all the three datasets except for health insurance which was only available in the 2011 and 2017-2018 datasets.…”
Section: Methodsmentioning
confidence: 99%
“…Women in urban regions have easier access to health facilities and maternal health intervention programs [ 21 23 ]. The makeup of the urban population in terms of wealth index, educational status, and other socioeconomic characteristics may also have a beneficial impact on the use of maternal health care services [ 24 26 ]. Research in Sub-Saharan Africa has revealed that women in urban regions utilize maternal health care more.…”
Section: Introductionmentioning
confidence: 99%